Validity of the severe impairment battery, brief praxis test, and dementia questionnaire for persons with intellectual disabilities in differentiating dementia status in individuals with Down syndrome: Neuropsychiatry and behavioral neurology/Dementia. (7th December 2020) - Wallace, Elizabeth; Harp, Jordan; Pelt, Kathryn L.; Koehl, Lisa; Caban‐Holt, Allison M.; Anderson‐Mooney, Amelia J; Robertson, William; Lightner, Donita; Jicha, Gregory A.; Head, Elizabeth; Schmitt, Frederick A.
Abstract: Background: Individuals with Down syndrome (DS) are at high risk for dementia, specifically Alzheimer's disease (AD). However, many measures regularly used for the detection of AD in the general population are not suitable for individuals with DS. Some measures, including the Severe Impairment Battery (SIB), Brief Praxis Test (BPT), and Dementia Questionnaire for Persons with Intellectual Disabilities (DMR), have been used in clinical trials and other research with this population. Validity research is limited, however, particularly regarding identification of predementia symptoms in the DS population. The current project presents baseline cross‐sectional SIB, BPT, and DMR performance in order to characterize their ability to discriminate normal cognition, possible AD, and probable AD in DS. Method: Baseline SIB, BPT, and DMR performances from 117 individuals were analyzed as part of a large longitudinal cohort of aging individuals with DS. Receiver operating characteristic (ROC) curves were calculated to investigate accuracy in differentiating levels of dementia status. Result: In comparing no/possible AD vs. probable AD, the SIB and BPT exhibited fair discrimination ability (AUC = .78 and .79, respectively). In comparing no/possible AD vs. probable AD, the DMR exhibited good discrimination ability (AUC = .89), with qualitatively similar performance of the DMR‐Cognitive and DMR‐Social subscales (AUC = .89 and .83, respectively). In comparing no AD vs. possible AD, the SIB and BPT failed to differentiate these groups (AUC = .53 and .55, respectively), whereas the DMR exhibited good differentiation (AUC = .80). Conclusion: Results suggest that the SIB, BPT, and DMR are able to discriminate between levels of dementia status in individuals with DS, supporting their continued use in the clinical assessment of dementia in DS. Specifically, the DMR, based on informant ratings of social and cognitive behaviors of daily living, outperformed the SIB and BPT, tests of cognitive performance, in discriminating no/possible AD vs. probable AD as well as no AD vs. possible AD. Such findings suggest that the DMR is better equipped to identify symptoms of overt dementia as well as predementia in this population. Findings reinforce the importance of including informant behavior ratings in assessment of this population.